Synthesis, in vitro and in silico studies on novel 3-aryloxymethyl-5-[(2-oxo-2-arylethyl)sulfanyl]-1,2,4-triazoles and their oxime derivatives as potent inhibitors of mPGES-1 - KULABAŞ, NECLA; TATAR, ESRA; KÜÇÜKGÜZEL, İLKAY; BİNGÖL ÖZAKPINAR, ÖZLEM (My University, 2023)
Human microsomal prostaglandin E synthase (mPGES)-1 is a glutathione-dependent membrane-bound enzyme which is involved in the terminal stage of prostaglandin E2 (PGE2) synthesis. It has been well reported as a key target for the discovery of new anti-inflammatory and anti-cancer drugs. Specific inhibitors of mPGES-1 are anticipated to selectively restrain the generation of PGE2 induced by the inflammatory stimuli, without obstructing of the regular biosynthesis of other homeostatic prostanoids. Therefore, the design of mPGES-1 inhibitors can represent a better choice to take control of PGE2 associated diseases, compared with conventional non-steroidal anti-inflammatory drugs and cyclooxygenase (COX) inhibitors, which are known for their serious side effects. Although there is an intensive effort for the identification of mPGES-1 inhibitors, none of the unveiled molecules so far have reached the clinical market. Therefore, the development of novel mPGES-1 inhibitors with proper drug-like properties is still an unmet medical need. As a continuation of our research for the identification of new chemotypes which might inhibit this enzyme, we now report the design and synthesis of 3-aryloxymethyl-5-[(2-oxo2-arylethyl)sulfanyl]-1,2,4-triazoles and their oxime derivatives as inhibitors of human mPGES-1. All synthesized compounds were characterized by FTIR, 1H NMR, 13C NMR (for compounds 12, 14, 15, 26, 27), HMBC (for compounds 6, 7, 8, 16, 19, 23, 28), and MS data. Twenty-four target compounds 7–30 were screened for their mPGES-1/COX-2 inhibitory activities as well as their cytotoxicity. Of these compounds, 20 and 24 showed potent mPGES-1 inhibition by IC50 values of 0.224±0.070 μM and 1.08±0.35 μM, respectively. These two compounds have also been observed to inhibit angiogenesis in matrigel tube formation assay with no toxicity toward HUVEC cells. In silico studies were also held to understand inhibition mechanisms of the most active compounds using molecular docking, molecular dynamics calculations and ADMET predictions.
Keywords: Eczacılık; Meslek Bilimleri; Farmasötik Kimya; Sağlık Bilimleri; Pharmacology and Therapeutics; Professional Sciences; Pharmaceutical Chemistry; Health Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Clinical Medicine (MED); Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Yaşam Bilimleri; Pharmacy; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides; Life Sciences; mPGES-1; Inflammation; Cancer; Angiogenesis; 1; 2; 4-triazoles; Molecular docking